Radix Polygoni Multiflori and Its Main Component Emodin Attenuate Non-Alcoholic Fatty Liver Disease in Zebrafish by Regulation of AMPK Signaling Pathway - Yu, Linyuan (Drug Des Devel Ther, 2020)
PURPOSE: Nonalcoholic fatty liver disease (NAFLD) has become a predictor of death in many diseases. This study was carried out to investigate the therapeutic effect of Radix Polygoni Multiflori Preparata (RPMP) and its main component emodin on egg yolk powder-induced NAFLD in zebrafish. Further investigation was performed to explore whether emodin was the main component of RPMP for the treatment of NAFLD as well as the underlying therapeutic mechanism of RPMP and emodin. METHODS: Zebrafish were divided into control group, egg yolk powder group, RPMP group and emodin group. The obesity of zebrafish was evaluated by body weight, body length and BMI. The content of lipid was detected by triglyceride (TG), total cholesterol (TC) reagent kit and the fatty acid was detected by nonesterified free fatty acids (NEFA) reagent kit. HE staining was used to detect the histological structure of liver. Whole-mount Oil red O staining and Frozen oil red O staining were carried out to investigate the lipid accumulation in liver. KEGG and STRING databases were performed to analyze the potential role of AMPK between insulin resistance (IR) and fatty acid oxidation. Western blot and RT-qPCR were carried out for mechanism research. RESULTS: RPMP and emodin significantly reduced zebrafish weight, body length and BMI. Both RPMP and emodin treatment could reduce the lipid deposition in zebrafish liver. RPMP significantly reduced the content of TG. However, emodin significantly reduced the contents of TG, TC and NEFA in zebrafish with NAFLD. The protein interaction network indicated that AMPK participated in both IR and fatty acid oxidation. Further investigation indicated that RPMP and emodin reduced hepatic lipogenesis via up-regulating the expressions of phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT2), amp-activated protein kinase alpha (AMPKα), proliferator-activated receptor alpha (PPARα), carnitine palmitoyl transferase 1a (CPT-1a) and acyl-coenzyme A oxidase 1 (ACOX1). CONCLUSION: These findings suggest that emodin is the main component of RPMP for the treatment of NAFLD, which is closely related to the regulation of AMPK signaling pathway which increases IR and fatty acid oxidation.